Alphabet juice the energies, gists, and spirits of letters, words, and combinations thereof, their roots, bones, innards, piths, pips, and secret parts, tinctures, tonics, and essences, with examples of their usage foul and savory - Blount, Roy Jr. 1941- (Farrar, Straus and Giroux, 2008)
After 40 years of making a living using words in every medium, print or electronic, Blount still can't get over his ABCs. In this book, he celebrates the juju, the sonic and kinetic energies of letters and their combinations.